Peran Ibu Kota sebagai Pusat Kegiatan Nasional dalam Mendukung Interaksi Keruangan Pada Area Hinterland - Edy Abdurrahman Syahrir (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Spatial existence in Southeast Sulawesi Province in land areas tends to be concentrated in each district capital. The macro regional conditions are focused on a certain center, namely Kendari City as the National Activity Center so that its development affects the hinterland area. This research aims to identify the level of strength of spatial interaction between Kendari City as a National Activity Center and its hinterland area, as well as the level of connectivity between Kendari City regions and its hinterland in supporting inter-regional development. The analytical method for this research uses Gravity Model Analysis and Centrality Index based on Konig-Shimbel. The results of this research show that the hinterland area with a strong level of interaction strength with Kendari City only occurs in the South Konawe Regency area with a value of 1,052,223,272 interaction units. Then the most strategic areas based on the results of the connectivity analysis are South Konawe Regency and East Kolaka Regency because they received the lowest Konig-Shimbel score (having a value of 1). Meanwhile, the other areas had the highest score and had the lowest strategic value with a value range between 2-7. Therefore, it is hoped that the results of this research can be a lesson for regional planners to better understand the importance of spatial interaction and easy accessibility between regions as a process of establishing positioning to create place prosperity and people prosperity.